Effects of ranolazine on wild-type and mutant hNa(v)1.7 channels and on DRG neuron excitability - Estacion, Mark (BioMed Central, 2010)
BACKGROUND: A direct role of sodium channels in pain has recently been confirmed by establishing a monogenic link between SCN9A, the gene which encodes sodium channel Na(v)1.7, and pain disorders in humans, with gain-of-function mutations causing severe pain syndromes, and loss-of-function mutations causing congenital indifference to pain. Expression of sodium channel Na(v)1.8 in DRG neurons has also been shown to be essential for the manifestation of mutant Na(v)1.7-induced neuronal hyperexcitability. These findings have confirmed key roles of Na(v)1.7 and Na(v)1.8 in pain and identify these channels as novel targets for pain therapeutic development. Ranolazine preferentially blocks cardiac late sodium currents at concentrations that do not significantly reduce peak sodium current. Ranolazine also blocks wild-type Na(v)1.7 and Na(v)1.8 channels in a use-dependent manner. However, ranolazine's effects on gain-of-function mutations of Na(v)1.7 and on DRG neuron excitability have not been investigated. We used voltage- and current-clamp recordings to evaluate the hypothesis that ranolazine may be effective in regulating Na(v)1.7-induced DRG neuron hyperexcitability. RESULTS: We show that ranolazine produces comparable block of peak and ramp currents of wild-type Na(v)1.7 and mutant Na(v)1.7 channels linked to Inherited Erythromelalgia and Paroxysmal Extreme Pain Disorder. We also show that ranolazine, at a clinically-relevant concentration, blocks high-frequency firing of DRG neurons expressing wild-type but not mutant channels. CONCLUSIONS: Our data suggest that ranalozine can attenuate hyperexcitability of DRG neurons over-expressing wild-type Nav1.7 channels, as occurs in acquired neuropathic and inflammatory pain, and thus merits further study as an alternative to existing non-selective sodium channel blockers.